Anterolateral knee ligament. A review of current concepts - Delgadillo, David (Revista Colombiana de ortopedia y traumatología, 2017)
Recently, there has been an increasing interest in a structure located at the anterolateral region of the knee due to its possible role in the rotational stability of the joint. The structure has been named the anterolateral ligament. To date, there are reports of studies related to its anatomy, histology, radiology, and biomechanics. The purpose of this review is to summarise the publications made between 2007 and 2015. Databases were reviewed for articles in English and Spanish languages, which mentioned the anterolateral ligament of the knee. A total of 27 articles in English language were found, of which 24 were original articles, 2 editorials, and 1 poster abstract. The anterolateral ligament of the knee is a real structure and independent from the articular capsule and the popliteal tendon that is present in almost all patients. The stability role of the anterior cruciate ligament seems to be supported due to the increase in tension during knee flexion and internal rotation. Evidence level: IV.